Development of Microlearning Based on Project Citizenship in Citizenship Learning to Improve Students' Civic Disposition - Dwi Agustina Rahayu; Ajar Dirgantoro; Nurna Listya Purnamasari; A.A Putu Eka Putra (Proceeding International Conference on Digital Education and Social Science, 2024)
This research aims to develop a Project Citizenship-based Microlearning learning model in Civic Education courses to improve students' civic disposition in higher education. By using the Research and Development (R&D) method based on the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), this research produces innovative learning media that is effective, flexible, and relevant to meet the needs of digital era students. The results showed that the majority of students (78%) felt that civic learning was too theoretical, and 82% wanted a more practical approach. Therefore, a microlearning module was designed with interactive content in the form of short videos, infographics, quizzes, and applicable citizenship projects. The product was validated by material and media experts with validity levels of 89% and 87% respectively. The implementation of this model involved 70 students and was carried out for six month. The evaluation results showed a significant increase in the aspects of civic disposition: civic knowledge (20%), civic skills (21%), civic responsibility (23%), and civic participation (26%). Microlearning-based learning provides time flexibility, while integration with project citizenship motivates students to contribute directly to social activities. In conclusion, the development of microlearning based on project citizenship is effective in improving students' civic disposition, with advantages in the form of concise, practical material delivery, and being able to build active involvement. This finding makes an important contribution to the innovation of Civic Education learning in the digital era.